Overview of clusters and diphthongs in the discourse of Rahovec and its district - Dulaj, Fridrik (Technium Social Sciences Journal, 2022)
The paper aims to reflect the state of clusters and diphthongs in the discourse of Rahovec and its district. The study methodology has been done through unstructured interviews and free conversations with the subjects. Whereas, the results show these types of clusters and diphthongs: vowel cluster ue, vowel cluster ye, cluster ie and je, cluster ae and oe as well as the transition of the group vo to va. Based on the findings of the study, we can come to the conclusion that the discourse of Rahovec with its district has an old origin from the Indo-European and Latin languages.